Research on Library Space Construction and Services under the Background of Smart Library - Wang, Fang (International Journal of Social Sciences and Public Administration, 2024)
The rapid development and application of the new generation of digital intelligence technology, as well as the continuous growth of users’ personalized needs, promote the continuous innovation and reform of library functions and services. Especially with the rise of the meta-universe, the service mode of traditional library is undergoing innovation and reshaping from document service to information service, knowledge service and space service. As a "constantly growing organism", in the process of accelerating technological upgrading and deepening humanistic concepts, the concept, connotation, characteristics and construction path of smart space also develop and change. This paper mainly studies the transformation of library space construction and service under the background of the development of new generation technology and the construction of smart library, so as to better guide the development of smart space.